Developing organoids: an interview with Alice Soragni on 3D biology at the interface of treating cancers and protein aggregation (Nature Portfolio, 2021)
Alice Soragni is an Assistant Professor in the Department of Orthopedic Surgery at UCLA and a member of the Jonsson Comprehensive Cancer Center. Originally from Italy, she received her PhD in Physical Chemistry from the ETH of Zurich and a postdoc with David Eisenberg (UCLA) before starting her independent lab in December 2016. In this Q&A, Dr. Soragni tells us about her research on organoids, importance of learning from peers while starting an independent research career and of creating inclusive and diverse lab practices.